A new Orient : from German scholarship to Middle Eastern studies in Israel - Levy, Amit; Makleff, Ron Mordechai (Waltham, Massachusetts : Brandeis University Press, 2024)
"This study seeks to examine the history of Zionist academic Orientalism in light of its German-Jewish background as a history of knowledge transfer stretching along an axis from Germany to Palestine"--
"A history of knowledge transfer of Oriental Studies stretching along an axis from Germany to Palestine/Israel. This study examines the history of Zionist academic Orientalism-referred to throughout as Oriental studies, the term contemporary English speakers would have used-in light of its German-Jewish background, as a history of knowledge transfer stretching along an axis from Germany to Palestine. The transfer, which took place primarily during the 1920s and 1930s, involved questions about the re-establishment, far from Germany, of a field of knowledge with deep German roots. Like other German-Jewish scholars arriving in Palestine at the time, some of the Orientalist agents of transfer did so out of Zionist conviction as olim (immigrants making aliyah, or literally "ascending" to the homeland), while others joined them later as refugees from Nazi Germany; both groups were integrated into the institutional apparatus of the Hebrew University. Unlike other fields of knowledge or professions, however, the transfer of Orientalist knowledge was unique in that the axis involved an essential change in the nature of its encounter with the Orient: from a textual-scientific encounter at German universities, largely disconnected from contemporary issues to a living, substantive, and unmediated encounter with an essentially Arab region-and the escalating Jewish-Arab conflict in the background. Within the new context, German-Jewish Orientalist expertise was charged with political and cultural significance it had not previously faced, fundamentally influencing the course of the discipline's development in Palestine and Israel"--
The Science of the Orient : The Beginnings of Oriental Studies at the Hebrew University -- "With its back to the Orient?" The School of Oriental Studies and the Question of the Arab Intellectuals -- Orient renewed : the Birth of Israeli Oriental Studies and the Diplomatic Mission -- Epilogue : "Truly, Jerusalem has one benefit : lying within the Orient."
Text in English, the original language is undetermined.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on October 29, 2024).
JSTOR
Keywords: Universiṭah ha-ʻIvrit bi-Yerushalayim. -- Makhon le-limude Asyah ṿe-Afriḳah.; Orientalism -- Study and teaching -- Israel -- History -- 20th century; Orientalism -- Study and teaching -- Germany -- History -- 20th century; Middle East -- Study and teaching -- Israel -- History -- 20th century; Middle East -- Study and teaching -- Germany -- History -- 20th century; Orientalisme -- Étude et enseignement -- Israël -- Histoire -- 20e siècle.; Orientalisme -- Étude et enseignement -- Allemagne -- Histoire -- 20e siècle.; Moyen-Orient -- Étude et enseignement -- Israël -- Histoire -- 20e siècle.; Moyen-Orient -- Étude et enseignement -- Allemagne -- Histoire -- 20e siècle.; HISTORY / Europe / Germany; HISTORY / Jewish; HISTORY / General